2007
DOI: 10.4049/jimmunol.178.10.6130
|View full text |Cite
|
Sign up to set email alerts
|

9-cis-Retinoic Acid (9cRA), a Retinoid X Receptor (RXR) Ligand, Exerts Immunosuppressive Effects on Dendritic Cells by RXR-Dependent Activation: Inhibition of Peroxisome Proliferator-Activated Receptor γ Blocks Some of the 9cRA Activities, and Precludes Them to Mature Phenotype Development

Abstract: At nanomolar range, 9-cis-retinoic acid (9cRA) was able to interfere in the normal differentiation process from human monocyte to immature dendritic cell (DC) and produced a switch in mature DCs to a less stimulatory mode than untreated cells. 9cRA-treated mature DCs secreted high levels of IL-10 with an IL-12 reduced production. The phenotypic alterations unleashed by 9cRA were similar but not identical to other specific retinoid X receptor (RXR) agonists and to those already reported for rosiglitazone, a PPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
49
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 80 publications
2
49
0
2
Order By: Relevance
“…Interestingly, stimulation of fully differentiated immature MoDCs with LXR agonists in combination with 9-cis-retinoic acid (9cRA), but in the absence of a maturation stimulus, was shown to induce CCR7 expression [38]. Thus, it is tempting to speculate that LXR agonists in combination with 9cRA, known to induce tolerogenic DCs [39], promotes tolerance in the absence of canonical "danger" Eur. J. Immunol.…”
mentioning
confidence: 99%
“…Interestingly, stimulation of fully differentiated immature MoDCs with LXR agonists in combination with 9-cis-retinoic acid (9cRA), but in the absence of a maturation stimulus, was shown to induce CCR7 expression [38]. Thus, it is tempting to speculate that LXR agonists in combination with 9cRA, known to induce tolerogenic DCs [39], promotes tolerance in the absence of canonical "danger" Eur. J. Immunol.…”
mentioning
confidence: 99%
“…Used systemically, it alters energy metabolism (15). 9cRA also shows promise in reducing ischemic brain injury in a rat model and in immunosuppressing human dendritic cells (16,17). Regardless of the pharmacological utility of 9cRA, sensitive assays capable of quantifying individual RA isomers in biological matrices have not detected 9cRA in serum and in a variety of tissues (18,19).…”
mentioning
confidence: 99%
“…The high number of IL-12 will stimulate T cell proliferation becomes Th cell and influence NK and Th1 and Th2 cell to secrete IFN-γ [23]. The results showed that IFN-γ levels also increased high enough, the highest production of it has been found in the mice which given 6 000 IU with vitamin A. IFN-γ which secreted will reactivate macrophages.…”
Section: Discussionmentioning
confidence: 95%